Circular - Stewart, Margaret, fl. 1938-
017b-0006-001 PARLIAMENTARY COMMITEE FOR SPAIN 11a BLOOMSBURY WAY, LONDON, W.C.1 Telephone: CHANCERY 8487. Richard Acland, M.P. Alfred Barnes, M.P. Vernon Bartlett, M.P. Aneurin Bevan, M.P. David Grenfell, M.P. Megan Lloyd-George, M.P. Geoffrey Le M. Mander, M.P. Philip Noel-Baker, M.P. D.N. Pritt, K.C. M.P. Eleanor Rathbone, M.P. S. Silverman, M.P. G.R. Strauss, M.P. Edith Summerskill, M.P. Rt. Hon. J.C. Wedgwood, M.P. Ellen Wilkinson, M.P. H. Graham White, M.P. Advisory Council: The Duchess of Atholl, D.B.E., D.C.L. The Lady Violet Bonham-Carter. Gerald Brenan. Mrs. Denis Browne. Sir Peter Chalmers-Mitchell, F.R.S. The Viscount Cecil of Chelwood, P.C., K.C. The Dean of Chichester. G.T. Garratt. W. Horsfall Carter. The Earl of Listowel. The Viscountess Rhondda The Lord Strabolgi. Professor J.B. Trend. Sir George Young, Bt. Hon Secretaries: JOHN JAGGER, M.P., WILFRID ROBERTS, M.P. All communications should be addressed to the Organising Secretary. Tel: Central 7147. 151, Fleet Street, London, E.C.4. 14th April, 1939. Dear Sir or Madam, I think you may be interested to see the enclosed material which was prepared by this Committee for the use of Members of Parliament: 1. A note on Italy's violations of the Anglo-Italian Agreement. 2. "The Prime Minister on British Relations with Italy". 3. Some Speakers' Notes, dealing mainly with General Franco's relation to the Axis. If you would like further copies of any of these publications, we should be very glad to send you some. Yours faithfully, Margaret Stewart Organising Secretary. 292/946/17b/6